The Pea Gene LH Encodes ent-Kaurene Oxidase - Davidson, Sandra E. (The American Society for Plant Biologists, 2004)
The pea (Pisum sativum) homolog, PsKO1, of the Arabidopsis GA3 gene was isolated. It codes for a cytochrome P450 from the CYP701A subfamily and has ent-kaurene oxidase (KO) activity, catalyzing the three step oxidation of ent-kaurene to ent-kaurenoic acid in the gibberellin (GA) biosynthetic pathway when expressed in yeast (Saccharomyces cerevisiae). PsKO1 is encoded by the LH gene because in three independent mutant alleles, lh-1, lh-2, and lh-3, PsKO1 has altered sequence, and the lh-1 allele, when expressed in yeast, failed to metabolize ent-kaurene. The lh mutants of pea are GA deficient and have reduced internode elongation and root growth. One mutant (lh-2) also causes a large increase in seed abortion. PsKO1 (LH) is expressed in all tissues examined, including stems, roots, and seeds, and appears to be a single-copy gene. Differences in sensitivity to the GA synthesis inhibitor, paclobutrazol, between the mutants appear to result from the distinct nature of the genetic lesions. These differences may also explain the tissue-specific differences between the mutants.